Non-Canonical Wnt Signaling Regulates Cochlear Outgrowth and Planar Cell Polarity via Gsk3β Inhibition - Landin Malt, Andre; Clancy, Shaylyn; Hwang, Diane; Liu, Alice; Smith, Connor; Smith, Margaret; Hatley, Maya; Clemens, Christopher; Lu, Xiaowei (Frontiers in Cell and Developmental Biology, 2021)
During development, sensory hair cells in the cochlea assemble a stereociliary hair bundle on their apical surface with planar polarized structure and orientation. We have recently identified a non-canonical, Wnt/G-protein/PI3K signaling pathway that promotes cochlear outgrowth and coordinates planar polarization of the hair cell apical cytoskeleton and alignment of hair cell orientation across the cochlear epithelium. Here, we determined the involvement of the kinase Gsk3b and the small GTPase Rac1 in non-canonical Wnt signaling and its regulation of the Planar Cell Polarity (PCP) pathway in the cochlea. We provided the first in vivo evidence for Wnt regulation of Gsk3b activity via inhibitory Ser9 phosphorylation. Furthermore, we carried out genetic rescue experiments of cochlear defects caused by blocking Wnt secretion. We showed that cochlear outgrowth was partially rescued by genetic ablation of Gsk3b but not by expression of stabilized b-catenin; while PCP defects, including hair bundle polarity and junctional localization of the core PCP proteins Fzd6 and Dvl2, were partially rescued by either Gsk3b ablation or constitutive activation of Rac1. Our results identify Gsk3b and likely Rac1 as downstream components of non-canonical Wnt signaling and mediators of cochlear outgrowth, hair cell planar polarity and localization of a subset of core PCP proteins in the cochlea.